The Quality of Training Staff for the Digital Economy of Russia within the Framework of STEAM Education: Problems and Solutions in the Context of Distance Learning - Tatyana Anisimova; Fairuza Sabirova; Olga Shatunova; Tatyana Bochkareva; Vladimir Vasilev (MDPI AG, 2022)
The purpose of this study is to analyze the problems of quality training of personnel for the digital economy of Russia during the pandemic within the framework of STEAM education and to identify their solutions with the help of the most effective distance learning tools. The research is based on a survey of 138 respondents (students of the Department of Mathematics and Natural Sciences of the Yelabuga Institute of the Kazan Federal University), who have mastered professional competencies in a distance learning format during the pandemic. The results of the survey confirmed the conclusion that distance learning tools such as Moodle, Google Classroom, and Microsoft Teams have shown their effectiveness and can be successfully used not only in the context of extreme situations, for example, a pandemic, but also as elements of blended learning while bringing variety to the forms of learning, and thereby strengthening the process of training STEAM education specialists. The scientific novelty of the study lies in a deep analysis of the distance learning tools used for training specialists for the digital economy of Russia, namely STEAM education specialists, based on the collection of information from students during the period of transformational changes in the pedagogical education system.